Stability of a confined swirling annular liquid layer with heat and mass transfer. (January 2017) - Fu, Qing-fei; Jia, Bo-qi; Yang, Li-jun
Highlights: Studied the stability of swirling annular layers in a tube with heat and mass transfer. Swirling layers become unstable at high conduction to evaporation heat flux ratios. The effect of controlling parameters on the stability has been discussed. The effects of confinement are opposite with and without heat and mass transfer. Abstract: A linear temporal stability of confined swirling annular liquid layers involving heat and mass transfer at the gas–liquid interface is presented in this paper. A normal-mode stability analysis that includes the effect of both swirling and heat transfer is performed. The flow in a gas-center coaxial swirl injector gives rise to the flow configuration explored in this work. The effects of various non-dimensional parameters on the instability of the flow are discussed. The heat transfer at the interface has been characterized by introducing a heat flux ratio between the conduction heat flux and the evaporation heat flux. The heat and mass transfer at the interface are found to destabilize the flow. Increasing confinement destabilizes the flow, which is opposite to the condition without heat and mass transfer.